Determinants of the international performance of services: a conceptual model - Christina Sichtmann; Ilka Griese; Maren Klein (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
Countless determinants of export success that are supposed to help managers reduce the failure rates of export ventures have been identified. Despite this abundance of studies, however, little is known about the determinants of the internationalization success of services. In this paper, based on prior studies focusing primarily on manufactured goods and the key characteristics distinguishing services from goods, a comprehensive conceptual model for the successful internationalization of services is developed.
Keywords: 330; Services; export performance; internationalization; success factors; Dienstleistungssektor; Internationaler Dienstleistungsverkehr; Export; Erfolgsfaktor